A synchronous photoautotrophic-heterotrophic biofilm cultivation mode for Chlorella vulgaris biomass and lipid simultaneous accumulation. (15th February 2022) - Huang, Yun; Li, Peirong; Huang, Yong; Xia, Ao; Zhu, Xun; Liao, Qiang
Abstract: Microalgae biofilm was a porous structure formed by the accumulation of microalgae cells. The cells in upper layer of biofilm could receive light for photosynthetic growth and meanwhile removed the inorganic nitrogen and phosphorus etc. From wastewater to cleaner biomass. While with the increase of biofilm thickness, light could not reach the underlayer, forming a natural dark area in the bottom of the biofilm for microalgae heterotrophic growth. The naturally formed synchronous photoautotrophic-heterotrophic microalgae growth environment realized the synchronization of biofilm growth and lipid enrichment. The transmission of metabolic gases made the biofilm loose and porous (120.18% increase on the biofilm porosity), which provided more channels for the transmission of nutrients. Due to the synchronous heterotrophic enrichment in the bottom layer of biofilm, the maximum growth rate of biomass cultivated under synchronous photoautotrophic-heterotrophic biofilm was 3.04 times higher than that of photo-autotrophic biofilm and lipid yield increased by 2.22 times. The proportion of photosynthetic autotrophy of cells in the biofilm increased with the increase of light intensity which made an increase of 33.45% in the growth rate of biofilm but with a price of 43.88% reducing in the lipid content. While, the increase of heterotrophic proportion in the biofilm realized the simultaneous enhancement of biomass density and lipid content. The biomass productivity increased to 55.81 g m −2 d −1 and the lipid content increased to 46.79% at the same time. Thus, it solved the contradictory between the growth of microalgae and the accumulation of lipid, and provided a new idea for the application of changing wastewater resources to clean biofuel. It would have an important significant to the development of low-carbon renewable and clean energy. Graphical abstract: Image 1 Highlights: Natural dark area formed in biofilm bottom for microalgae heterotrophic growth. Transmission of metabolic gases made the biofilm loose for nutrients transmission. Synchronous photo-heterotrophic growth realized syn. biomass and lipid enrichment The maximum growth rate of photo-heterotrophic biofilm increased by 304%. The lipid yield of photo-heterotrophic biofilm increased by 2.22 times synchronously.